EKSTRAKSI FITUR CITRA API BERBASIS EKSTRAKSI WARNA PADA RUANG WARNA HSV dan RGB - Denny Hardiyanto; Dyah Anggun Sartika (LPPM STMIK El Rahma Yogyakarta, 2018)
The potential for fires increased at this time. Many factors cause fire, both small sale and large scale, such as forest fires. Early detection of fire is one of the right solutions. The Research about detection fire use any methods, you can use UAVs (Unmanned Aerial Vehicle), Android devices, and other technologies that are mostly based on image processing. This is one of the research based on image processing with fire objects. Fire image will be processed in the features extraction with the source of the fire coming from the candle. The candle is used as a detection object because the color characteristics of the fire in the candle as same as a larger scale fire. The method used is feature extraction based on colour extraction in HSV color space (Hue Saturation Value) and RGB color space (Red Green Blue). The result of this research are parameters of each color space for fire detection, there are HSV color space get 0,2≥Hue≥0,1; 0,85≥Saturation≥0,5; and 1≥Value≥0,9, and also for RGB color space get 255≥Red≥230; 250≥Green≥100; and 130≥Blue.